Training for Mothers at BKMM Coblong District to Improve Family Education and Economics - Y. Yuliany; Ida Nursida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The urgency in this research relates to the training of mothers in BKMM Coblong District and Sadang Serang, Sekeloa, Lebak Gede, Dago, Lebak Siliwangi and Cipaganti sub-districts, Bandung City. The aim of this research is to find out various trainings for mothers in the BKMM area of ​​Coblong District so that they can improve education and the family economy which is beneficial for everyday life. The research method used is descriptive qualitative through literature review, observation, and interview techniques, which collect and process relevant data centrally from BKMM in the Coblong District area to obtain benefits in social life. BKMM facilitates training such as routine recitation, family management, making laundry soap from used cooking oil, classifying library books, putting on make-up, wearing the hijab, planting fruit in pots, and providing halal labels for food and beverage products. This training empowers women to improve the quality of family life. The results obtained in this research show that most mothers in Coblong District have received training. Still, several mothers in the al-Muslim, Al-Mubarok, and Al-Barokah mosques have not received training because the three mosques are currently under renovation. The conclusion of this research states that the BKMM training program in Coblong District is part of DMI which can empower women through improving skills, Islamic religious education, and empowering the family economy to create a prosperous society.